2020
DOI: 10.1111/iwj.13393
|View full text |Cite
|
Sign up to set email alerts
|

Are high‐risk patient and revision arthroplasty effective indications for closed‐incisional negative‐pressure wound therapy after total hip or knee arthroplasty? A systematic review and meta‐analysis

Abstract: To determine the effective indications of closed‐incisional negative‐pressure wound therapy (ciNPWT) following total hip or knee arthroplasty, this systematic review and meta‐analysis was conducted. The systematic search was performed on MEDLINE, Embase, and Cochrane Library, and 11 studies were included. The studies comparing between ciNPWT and conventional dressings were categorised into following subgroups based on patient risk and revision procedures: routine vs high‐risk patient; primary vs revision arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
(129 reference statements)
1
12
0
Order By: Relevance
“…Also, additional studies are required to provide a clinically meaningful difference in the outcomes. This was also suggested in previous similar meta‐analysis studies, which showed a similar effect of negative pressure wound therapy and conventional wound dressings in subjects with different types of orthopaedic trauma surgery 32‐40 . The insignificant results of negative pressure wound therapy in the length of hospital stay also need additional study and clarification because no clear reasoning was found to clarify these outcomes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Also, additional studies are required to provide a clinically meaningful difference in the outcomes. This was also suggested in previous similar meta‐analysis studies, which showed a similar effect of negative pressure wound therapy and conventional wound dressings in subjects with different types of orthopaedic trauma surgery 32‐40 . The insignificant results of negative pressure wound therapy in the length of hospital stay also need additional study and clarification because no clear reasoning was found to clarify these outcomes.…”
Section: Discussionmentioning
confidence: 66%
“…This was also suggested in previous similar meta-analysis studies, which showed a similar effect of negative pressure wound therapy and conventional wound dressings in subjects with different types of orthopaedic trauma surgery. [32][33][34][35][36][37][38][39][40] The insignificant results of negative pressure wound therapy in the length of hospital stay also need additional study and clarification because no clear reasoning was found to clarify these outcomes. Wellconducted studies are also required to measure these factors and the blend of different ages and ethnicity, because our meta-analysis study could not answer whether they are related to the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis of 11 studies on ciNPWT in knee or hip arthroplasty (including 8 randomized trials and 3 comparative cohort studies) found that ciNPWT could significantly reduce the incidence of wound complication and SSI in high-risk patients, and patients undergoing revision arthroplasties when compared with conventional dressing [ 25 ]. Among the high-risk patients, the ciNPWT cohort had significantly lower rates of wound complication (OR = 0.38, p = 0.030) and SSI (OR = 0.24, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Wound leakage is a sign of persistent infection and requires repeat debridement [ 22 ]. Negative-pressure wound therapy (NPWT) could be used in medically unfit patients, but its effectiveness is unknown [ 12 , 23 , 24 , 25 , 26 ]. In general, outcome studies in patient groups with PJIs are hard to compare due to their heterogeneous characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…For the management of PJIs and to predict the outcome of PJIs, all potential risk factors should be considered and evaluated [ 3 ]. There are several reported studies about factors associated with the treatment outcome in patients with spacer implantation as the first-stage procedure [ 17 , 26 ]. However, there is limited literature available regarding possible risk factors associated with failed resection arthroplasties as a first-stage procedure.…”
Section: Introductionmentioning
confidence: 99%